The transcription factor MebHLH18 in cassava functions in decreasing low temperature-induced leaf abscission to promote low-temperature tolerance - Liao, Wenbin; Cai, Jie; Xu, Haixia; Wang, Yilin; Cao, Yingjie; Ruan, Mengbin; Chen, Songbi; Peng, Ming (Frontiers in Plant Science, 2023)
The reactive oxygen species (ROS) signal regulates stress-induced leaf abscission in cassava. The relationship between the function of the cassava transcription factor bHLH gene and low temperature-induced leaf abscission is still unclear. Here, we report that MebHLH18, a transcription factor, involved in regulating low temperature-induced leaf abscission in cassava. The expression of the MebHLH18 gene was significantly related to low temperature-induced leaf abscission and POD level. Under low temperatures, the levels of ROS scavengers in different cassava genotypes were significantly different in the low temperature-induced leaf abscission process. Cassava gene transformation showed that MebHLH18 overexpression significantly decreased the low temperature-induced leaf abscission rate. Simultaneously, interference expression increased the rate of leaf abscission under the same conditions. ROS analysis showed a connection between the decrease in the low temperature-induced leaf abscission rate caused by MebHLH18 expression and the increase in antioxidant activity. A Genome-wide association studies analysis showed a relationship between the natural variation of the promoter region of MebHLH18 and low temperature-induced leaf abscission. Furthermore, studies showed that the change in MebHLH18 expression was caused by a single nucleotide polymorphism variation in the promoter region upstream of the gene. The high expression of MebHLH18 led to a significant increase in POD activity. The increased POD activity decreased the accumulation of ROS at low temperatures and the rate of leaf abscission. It indicates that the natural variation in the promoter region of MebHLH18 increases antioxidant levels under low temperatures and slows down low temperature-induced leaf abscission.